2017
DOI: 10.1007/s00784-017-2064-8
|View full text |Cite
|
Sign up to set email alerts
|

Marginal and internal fit of posterior three-unit fixed zirconia dental prostheses fabricated with two different CAD/CAM systems and materials

Abstract: Both investigated systems showed clinically acceptable values within the limitations of this in vitro study. However, one showed less internal accuracy when regular zirconia was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 29 publications
1
22
0
6
Order By: Relevance
“…However, when the extraoral (Group 3) and intraoral (Group 4) CAD/CAM system groups were compared, there was no difference between them in terms of vertical marginal adaptation. Similar results were found in other studies (16,17).…”
Section: Discussionsupporting
confidence: 93%
“…However, when the extraoral (Group 3) and intraoral (Group 4) CAD/CAM system groups were compared, there was no difference between them in terms of vertical marginal adaptation. Similar results were found in other studies (16,17).…”
Section: Discussionsupporting
confidence: 93%
“…The results might not be fully representative for the procedures available today. The soft-and hardware of the CAD/CAM technology has significantly evolved in the last decade, and the accuracy of the procedures has been improved [25]. Internal gap values of zirconia FDP frameworks in the literature ranged from 140(±26)µm in laboratory studies and 130(±56)µm in clinical studies [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have evaluated the fit of various superstructures produced by the Ceramill system and reported similar, or reduced, levels of misfit compared with those found in this study. Schönberger et al reported a statistically significant difference in terms of internal and marginal fits of the frameworks with the Ceramill system compared with Cercon CAD/CAM systems. Ceramill frameworks exhibited a median adaptation marginal gap value of 21 μm, while Cercon had a value of 27 μm.…”
Section: Discussionmentioning
confidence: 99%
“…The misfit values of CAD/CAM crowns fabricated using the CEREC system are reported to be in the range of 72 to 247 μm, whereas the Ceramill system is reported to exhibit a misfit range of 30 to 77 μm . However, a direct comparison of the two systems in terms of implant‐supported crown adaptation under the same conditions and using the same materials has not been reported.…”
mentioning
confidence: 99%